Taphonomy of Bouchardia rosea (Rhynchonelliformea, Brachiopoda) shells from Ubatuba Bay, Brazil: implications for the use of taphonomic signatures in (paleo)environmental analysis - Coelho Rodrigues, Sabrina; Guimaraes Simoes, Marcello [UNESP] (Asociacion Paleontologica Argentina, 2010)
This study analyzes taphonomic alteration of brachiopod shells, i.e., Bouchardia rosea (Mawe) from Ubatuba Bay, northern coast of São Paulo State, Brazil. The average age of the studied shell deposits is 674 years BP. The underlying hypothesis is that taphonomic signatures are not uniformly distributed along a bathymetric gradient. Assemblages were sampled using a Van Veen grab sampler (31 x 40cm) along transect of fourteen stations from zero (beach) to 35 m water depth. Four sedimentary environments were recognized: (a) beach, (b) protected bay with clay bottom, (c) protected bay with sandy bottom, and (d) inner shelf with sandy bottom. All brachiopod shells (i.e., total fraction including fragments) from each of the five stations with appreciable accumulations (up to 1607 shells) were investigated following a protocol of ten taphonomic signatures. Six of these ten taphonomic signatures (articulation, fragmentation, edge alteration, color alteration, bioerosion, and encrustation) were homogeneously distributed among studied environments, indicating that these general types of taphonomic signatures per se are not sensitive to environmental conditions in this case. on the other hand, shell surface texture varied along the bathymetric gradient, thus showing a high potential to be used in taphofacies analyses. Several examples of taphonomic generalizations available in the literature are neither applicable nor comparable to our results, which further confirm that overgeneralizations should be avoided in taphonomic studies.
Keywords: Bouchardia rosea; Brachiopods; Taphonomic signatures; Shell texture; Ubatuba Bay; Holocene